Islamic Strategic Management in Islamic Educational Institutions: Bibliometric Analysis - Arridha Harahap; Indrianawati Usman (Global Education Journal, 2026)
This study aims to look at research mapping related to the theme of Islamic strategic management in educational institutions. In this study, the results of the identification of researchers who conduct research related to the management of Islamic strategies in educational institutions, developing themes and journals that publish with related themes are presented. The method used in this study is bibliometric. The articles used as data were 72 articles published in the pages of the Scopus indexed journal. The data was processed using biblioshyni R to be able to map bibliometric research themes related to the management of Islamic strategies in educational institutions. The results of the study show that the most productive journal that discusses Islamic strategic management in educational institutions is Islamic education journals. Meanwhile, the most impactful journal with the highest h-index is the International Journal of Education Development. The study also found that the development of journals that have published articles related to Islamic strategic management in educational institutions has increased significantly over the past 10 years. Huda is the author who has conducted the most research on strategic management in educational institutions by producing as many as 2 articles, in the span of 2016 and 2022. If viewed in terms of affiliation, then Universiti Kebangsaan Malaysia is an affiliate that conducts a lot of research with the keyword Islamic strategy management in educational institutions as many as 5 articles. Richardson is the author whose article was widely cited published in 2004 in the International Journal of Education Development under the title "Possibel Influences of Arabic-Islamic Culture on the Relective Practices Proposed For An Education Degree at The Higher Collages of Technology in The United Arab Emirates". In the keyword analysis, the term "Islamic" top-ranked was mentioned 36 times. Like the growth in article production, there has been a significant increase in the development of keywords related to Islamic strategic management in educational institutions. Furthermore, this study identifies trends in keyword development based on their centrality and density. This study discusses the trends and development of Islamic strategic management literature in educational institutions that have not been widely done. single paragraph of about 250 words maximum. The limitation of this research is that it only uses articles derived from the scopus page collected on September 5, 2023 with the research area of Islamic strategic management in educational institutions.